Nurses’ Perspectives on Sleep Promotion Practices in Indonesian ICUs: A Multicenter Cross-Sectional Study - Setiyarini, Sri; Listyaningrum, Desy; Hersinta Retno Martani; Sujalmo, Purwadi; Kusumawati, Happy Indah (Chakra Brahmanda Lentera Institute, 2025)
Background: Critically ill patients commonly experience sleep disturbance, which has the potential to increase mortality and morbidity. Therefore, implementing interventions to enhance sleep quality is crucial. This study aimed to explore Indonesian nurses' perceptions of patients' sleep and to investigate the relationship between sleep promotion practices and the quality of sleep of patients in the Intensive Care Unit (ICU). Methods: : A cross-sectional study design was used. A total of 211 nurses working in 10 ICU settings across 14 hospitals in Indonesia were involved using convenience sampling. The SLEEPii questionnaire was used to collect data from nurses who work in ICU for a minimum of one year. Data was analyzed using frequency, mean (±SD), Median (±IQR), the Spearman Rank test, Kendal tau, and Kruskal-Wallis test. This study was reported in accordance with the STROBE guidelines. Results: 211 nurses from 14 hospitals in Indonesia reported that critically ill patients had sleep duration less than four hours (46.4%) and had fair sleep quality (58.8%). Sleep duration had significant differences between hospital status (p=0.004), and general hospital classification (0.002). Significant differences were also reported between sleep quality with ICU number of each Hospital (p=0.023), hospital status (p=0.047), and general hospital classification (0.032). Even though all participant reported that none of the ICU have protocol to promote sleep, this study found that duration of sleep correlate with control environmental noise levels (p=0.036), receiving medications for sleep (p=0.021), and activity to keeping ICU rooms dark at night (p=0.043), adhere to a clustered sleep protocol designed (p=0.001) and create conditions for a dedicated sleeping (p=0.004). Controlling environmental noise levels also correlated with sleep quality. Conclusion: Most of the critically ill patients had fair sleep quality. Findings suggest the urgent need for standardized sleep promotion protocols in Indonesian ICUs.